Brevundimonas and Serratia as host systems for assessing associated environmental viromes and phage diversity by complementary approaches - Friedrich, Ines; Neubauer, Hannes; Kuritsyn, Alisa; Bodenberger, Bernhard; Tskhay, Faina; Hartmann, Sara; Poehlein, Anja; Bömeke, Mechthild; Hoppert, Michael; Schneider, Dominik; Hertel, Robert; Daniel, Rolf (Frontiers in Microbiology, 2023)
Focusing on visible plaques for phage isolation leaves the question if we miss the diversity of non-plaque forming phages. We addressed this question through direct plaque-based isolation by employing the new hosts Brevundimonas pondensis LVF1 and Serratia marcescens LVF3 dsDNA, ssDNA, dsRNA, and ssRNA host-associated metavirome analysis. Of the 25 distinctive dsDNA phage isolates, 14 were associated with Brevundimonas and 11 with Serratia. TEM analysis revealed that 6 were myoviruses, 18 siphoviruses and 1 podovirus, while phages infecting Brevundimonas belonged all to siphoviruses. The associated viromes isuggested a higher phage diversity in summer than in winter, and dsDNA phages were the dominant group. Isolation of vB_SmaP-Kaonashi was possible after investigating the viromes associated with Serratia, demonstrating the great potential of accompanying host-associated metavirome analysis. The ssDNA virome analysis showed that the B. pondensis LVF1 host is associated with Microviridae and Inoviridae phages, although none of them were isolated. The results demonstrated that the classical isolation technique is not exhausted, leading to the isolation of new dsDNA phages. It can be further improved by combination with metavirome techniques, which revealed further diversity.